Low-ash anthracite-based porous carbon and a method for preparing the same
Patent Information
- Application Number
- CN202611058148.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-16
- Publication Date
- 2026-08-28
AI Technical Summary
目前工业化及专利公开的无烟煤基多孔炭制备工艺主要分为两类:其一为强碱化学活化法,普遍采用无烟煤与KOH、NaOH高温共混活化,该方法比表面积提升效果显著,但存在炭烧损率高、成品收率低、强碱高温严重腐蚀窑炉衬体、钾盐杂质残留高、后续酸洗负荷极大等缺陷,其二为单一物理活化法,采用水蒸气、二氧化碳单一气氛高温活化,工艺无强碱污染,但存在造孔效率低、微孔占比过高、介孔缺失、孔结构单一、吸附传质性能差等问题,产品性能难以满足高端应用场景
本发明公开的低灰分无烟煤基多孔炭制备方法,采用前置脱灰、低温熔盐嵌孔、梯度气氛活化、双酸分步酸洗耦合工艺,制备出微孔-介孔协同分布、灰分极低、吸附性能优异、收率显著提升的多级孔无烟煤基多孔炭,完全摒弃现有无烟煤多孔炭主流的强碱活化、单一物理活化路线,全程未添加KOH、NaOH、ZnCl2等传统化学活化剂;
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion battery anode material technology, specifically disclosing a low-ash anthracite-based porous carbon and its preparation method. Background Technology
[0002] Anthracite, due to its high fixed carbon content, dense structure, and low raw material cost, is an excellent precursor for preparing high-performance porous carbon. Currently, industrialized and patented anthracite-based porous carbon preparation processes mainly fall into two categories: The first is the strong-alkali chemical activation method, which commonly uses high-temperature co-activation of anthracite with KOH and NaOH. This method significantly improves the specific surface area, but suffers from drawbacks such as high carbon burn-off rate, low product yield, severe corrosion of the kiln lining by strong alkali at high temperatures, high potassium salt impurity residue, and extremely high subsequent acid washing load. The second is the single physical activation method, which uses a single atmosphere of steam and carbon dioxide for high-temperature activation. This process avoids strong alkali pollution, but suffers from low pore-forming efficiency, excessively high micropore ratio, lack of mesopores, simple pore structure, and poor adsorption and mass transfer performance, making it difficult for the product performance to meet the needs of high-end applications.
[0003] Meanwhile, existing technologies have core process defects: most processes involve high-temperature activation followed by acid washing to remove impurities. The original silicon-aluminum and calcium-magnesium minerals inside the anthracite are encapsulated by high-temperature carbonization and solidification, which is difficult to completely remove by conventional acid washing, resulting in high ash content in the finished product. Furthermore, traditional processes use a single activation atmosphere and a temperature-progressive solidification process, which cannot achieve controllable hierarchical regulation of micropores and mesopores, resulting in poor product versatility. Summary of the Invention
[0004] To address the problems in the background art, this invention discloses a low-ash anthracite-based porous carbon and its preparation method. The method employs a pre-ashing process, low-temperature molten salt pore embedding, gradient atmosphere activation, and a dual-acid stepwise acid washing coupling process to prepare a multi-level porous anthracite-based porous carbon with micropore-mesopore synergistic distribution, extremely low ash content, excellent adsorption performance, and significantly improved yield.
[0005] To achieve the above-mentioned objectives, the present invention adopts the following technical solution: A method for preparing low-ash anthracite-based porous carbon specifically includes the following steps: Step 1: Take high-rank anthracite, coarsely crush it, and then put it into a planetary ball mill to grind it to 300-400 mesh to obtain material 1; Step 2: Add the modifying agent to material 1, and then use dry mechanical chemical ball milling for 2-4 hours to obtain material 2; Step 3: Mix and soak material 2 with acid solution to dissolve the calcium, magnesium and iron inorganic mineral impurities trapped in the anthracite coal, filter to obtain filter cake, wash the filter cake with deionized water several times and then dry it to obtain pre-deashed clean coal powder. Step 4: Mix the pre-deashed clean coal powder prepared in Step 3 with the eutectic composite molten salt at a mass ratio of 1:0.8-1.2 using a uniform dry method to obtain the mixed powder. Step 5: Place the mixed powder prepared in Step 4 in a sealed oven and keep it at a constant temperature of 230-250℃ for 3-8 hours. The composite molten salt will completely melt and penetrate into the pores inside the coal powder, forming a uniformly distributed nano-salt crystal occupant template in situ inside the carbon matrix. After natural cooling, crush and granulate the mixture, and screen out granules with a particle size of 10-40 mesh to obtain the molten salt-embedded porous carbon precursor. Step Six: Place the porous carbon precursor prepared in Step Five into a rotary kiln or tubular furnace, and activate and carbonize it using a three-stage gradient heating and segmented atmosphere switching process at a heating rate of 4℃ / min. The temperature curve is as follows: The first stage, the inert pre-carbonization stage: high-purity nitrogen gas is introduced into the rotary kiln or tubular furnace, the temperature is raised to 550℃, and the temperature is kept constant for 60-90 minutes to complete the low-temperature carbonization of the anthracite organic matter, precipitate small molecule side chains, initially construct the original pores, and stabilize the internal molten salt grains. The second stage, the weak oxidation pore repair stage: the atmosphere in the rotary kiln or tube furnace is switched to a weak oxidation mixture of nitrogen + (3~5) vol% dry air. The temperature in the rotary kiln or tube furnace is raised from 550℃ to 750℃ and kept at a constant temperature for 60~90min. A small amount of weak oxidation etches the non-amorphous defect sites of the carbon material, widening the original micropores without causing a large amount of carbon matrix burn-off. The third stage, CO2 fine pore expansion stage: The atmosphere in the rotary kiln or tubular furnace is switched to pure carbon dioxide atmosphere, the temperature in the rotary kiln or tubular furnace is raised from 750℃ to 880℃, and the temperature is kept constant for 120-180 minutes. Carbon dioxide selectively etches the edge of the pores, precisely expands the mesoporous structure, and forms micropore-mesopore composite pores. After activation, the furnace is naturally cooled to room temperature under nitrogen protection atmosphere and then removed from the furnace to obtain molten salt coated porous carbon crude product. Step 7: Pickling the porous carbon crude product coated with molten salt removes molten salt and mineral impurities. The solid material after removing molten salt and mineral impurities is rinsed multiple times with deionized water until the pH of the rinsing wastewater is 6.5-7.2 and there are no soluble salt residues. Filter and separate the solid and liquid. Step 8: Place the rinsed carbon material filter cake in a vacuum drying oven and dry it at 120℃ for 2-10 hours to avoid pore collapse caused by high-temperature drying at normal pressure; then place the material in a nitrogen atmosphere furnace and passivate it at 760℃ for 40-90 minutes. Finally, crush, classify, sieve, and demagnetize to obtain the anthracite-based porous carbon anode product.
[0006] Furthermore, in the method for preparing low-ash anthracite-based porous carbon, in step one, the mass percentage of fixed carbon in the anthracite is 82%–90%, and the ash content of the anthracite is 7–15%.
[0007] Furthermore, in the method for preparing low-ash anthracite-based porous carbon, in step two, the additive is a mixture of citric acid and ammonium fluoride powder, with the amount of citric acid added being 1.0 wt% of the coal powder mass and the amount of ammonium fluoride added being 2.5 wt% of the coal powder mass.
[0008] Furthermore, in the method for preparing low-ash anthracite-based porous carbon, in step three, the ash content of the pre-deashed clean coal powder is 0.8% to 1.8%.
[0009] Furthermore, in the method for preparing low-ash anthracite-based porous carbon, in step three, material two is mixed with 3-5 wt% dilute sulfuric acid at a solid-liquid ratio of 1:6, stirred and soaked in a water bath at 50℃-80℃ for 4-6 hours, filtered to obtain a filter cake, and washed multiple times with deionized water until the pH of the washing solution is 6.0-7.0. The washed filter cake is then dried at a constant temperature of 110℃ for 2-10 hours.
[0010] Furthermore, in the method for preparing low-ash anthracite-based porous carbon, in step four, the composite molten salt is a mixture of anhydrous potassium acetate and magnesium nitrate mixed in a mass ratio of 7:3, and the eutectic point of the composite molten salt is 215℃.
[0011] Furthermore, in the method for preparing low-ash anthracite-based porous carbon, in step five, the vacuum degree of the sealed oven is -0.08 MPa.
[0012] Furthermore, in the method for preparing low-ash anthracite-based porous carbon, the specific acid washing step in step seven is as follows: First-stage sulfuric acid removal of molten salt: Mix the porous carbon crude product with 5wt% dilute sulfuric acid at a solid-liquid ratio of 1:7, stir and acid wash at 80℃ for 2-5 hours to completely convert the molten salt inside the porous carbon crude product into water-soluble salts and dissolve them. Filter to complete the preliminary solid-liquid separation. Secondary hydrochloric acid demineralization: The acid-washed solid material is mixed with 4wt% dilute hydrochloric acid and soaked at room temperature for 2-5 hours to dissolve the potassium aluminum silicate and alumina insoluble mineral impurities remaining in the carbon matrix. After filtration, the secondary solid-liquid separation is completed.
[0013] A low-ash anthracite-based porous carbon, wherein the low-ash anthracite-based porous carbon is prepared by the above-described method for preparing low-ash anthracite-based porous carbon.
[0014] Furthermore, the particle size of the low-ash anthracite-based porous carbon is D10: ≥4.5μm, D50: 7.0-8.0μm, D90≤15μm, and D100≤20μm.
[0015] Compared with the prior art, the beneficial effects of the present invention are: The method for preparing low-ash anthracite-based porous carbon disclosed in this invention employs a pre-ashing, low-temperature molten salt pore-embedding, gradient atmosphere activation, and dual-acid stepwise acid washing coupled process to prepare multi-level porous anthracite-based porous carbon with micropore-mesopore synergistic distribution, extremely low ash content, excellent adsorption performance, and significantly improved yield. It completely abandons the mainstream strong alkali activation and single physical activation routes of existing anthracite porous carbon, and does not add traditional chemical activators such as KOH, NaOH, and ZnCl2 throughout the entire process. This invention discloses a method for preparing low-ash anthracite-based porous carbon. It employs a pre-treatment logic of deashing, pore formation, and activation, overturning the traditional process sequence of acid washing after activation. It also eliminates the excessive carbon burning defect of traditional strong alkali high-temperature etching pore formation, instead using low-temperature physical molten salt for site-specific pore formation. The finished carbon yield can reach 32%–38%, an improvement of 7–13 percentage points compared to the traditional strong alkali activation process, significantly increasing raw material utilization. A three-stage gradient atmosphere coupled with low-temperature molten salt physical pore formation enables precise control of the pore structure. The prepared porous carbon achieves a multi-level synergistic distribution of micropores and mesopores, overcoming the single pore structure defect of traditional processes. It balances adsorption capacity and mass transfer efficiency, achieving a specific surface area of 2000–2200 m² / g and a stable ash content below 1.2%, far superior to products from traditional processes. Stepwise acid washing with sulfuric acid and hydrochloric acid removes molten salt impurities and primary mineral impurities separately, achieving a much higher impurity removal precision than a single acid washing process. The method for preparing low-ash anthracite-based porous carbon disclosed in this invention has no high-temperature strong alkali corrosion system throughout the entire process, which greatly reduces the corrosion loss of the mullite and corundum linings of the kiln, reduces equipment damage and maintenance costs, and removes impurities through step-by-step acid washing. The waste liquid has a single composition and can realize the resource recovery of potassium and magnesium salts, making it more environmentally friendly and reducing environmental treatment costs. The parameters of each process are stable and highly controllable, and it can be adapted to mainstream industrial equipment such as tube furnaces and rotary kilns. It can mass-produce high, medium and low specific surface area multi-level porous carbon products, which are suitable for high-end adsorption and energy storage material applications. Detailed Implementation
[0016] To better understand the present invention, the following embodiments further illustrate the content of the invention, but the scope of protection of the present invention is not limited to the following embodiments. Numerous specific details are set forth in the following description to provide a more thorough understanding of the invention. However, it will be apparent to those skilled in the art that the present invention can be practiced without one or more of these details. Example 1
[0017] A method for preparing low-ash anthracite-based porous carbon specifically includes the following steps: Step 1: Take high-rank anthracite. The fixed carbon content in the anthracite is 86% by mass, and the ash content is 11.2%. After coarse crushing, put it into a planetary ball mill and crush it to 350 mesh to obtain material 1. Step 2: Add a modifying agent to material 1. The agent is a mixture of citric acid and ammonium fluoride powder. The amount of citric acid added is 1.0 wt% of the coal powder mass, and the amount of ammonium fluoride added is 2.5 wt% of the coal powder mass. Then, use dry mechanical chemical ball milling for 3 hours to obtain material 2. Step 3: Mix material 2 with 4wt% dilute sulfuric acid at a solid-liquid ratio of 1:6, stir and soak in an 80℃ water bath for 5 hours to dissolve the calcium, magnesium, and iron inorganic mineral impurities trapped in the anthracite, filter to obtain filter cake, wash the filter cake multiple times with deionized water until the pH of the washing solution is 6.2, dry at 110℃ for 5 hours to obtain pre-deashed clean coal powder, the ash content of the pre-deashed clean coal powder is 1.2%; Step 4: Mix the pre-deashed clean coal powder prepared in Step 3 with the low eutectic composite molten salt in a uniform dry method at a mass ratio of 1:1.0 to obtain a mixed powder. The composite molten salt is a mixture of anhydrous potassium acetate and magnesium nitrate mixed in a mass ratio of 7:3. The eutectic point of the composite molten salt is 215℃. Step 5: Place the mixed powder prepared in Step 4 in a sealed oven with a vacuum degree of -0.08MPa and keep it at a constant temperature of 240℃ for 3 hours. The composite molten salt will completely melt and penetrate into the internal pores of the coal powder, forming uniformly distributed nano-salt crystal occupant templates in situ inside the carbon matrix. After natural cooling, crush and granulate the material, and screen out granules with a particle size of 10-40 mesh to obtain the molten salt-embedded porous carbon precursor. Step Six: Place the porous carbon precursor prepared in Step Five into a rotary kiln, and introduce high-purity nitrogen gas into the rotary kiln at a rate of 4℃ / min. The temperature is raised to 550℃ and held at that temperature for 90 minutes to complete the low-temperature carbonization of anthracite organic matter, precipitating small molecule side chains, initially constructing original pores, and stabilizing the internal molten salt grains. The atmosphere in the rotary kiln is then switched to a weakly oxidizing mixture of nitrogen and 4 vol% dry air, and the temperature inside the rotary kiln is raised to 750℃ and held at that temperature for 60 minutes. A small amount of weak oxidation etches the amorphous defect sites of the carbon material, widening the original micropores without causing a large amount of carbon matrix burn-off. Then, the atmosphere in the rotary kiln or tubular furnace is switched to a pure carbon dioxide atmosphere, and the temperature inside the rotary kiln is raised to 880℃ and held at that temperature for 150 minutes. Carbon dioxide selectively etches the pore edges, precisely amplifying the mesoporous structure and forming micropore-mesopore composite channels. After activation, the material is naturally cooled to room temperature under a nitrogen protective atmosphere and then removed from the furnace to obtain crude molten salt-coated porous carbon. Step 7: Using a segmented acid washing process, the porous carbon crude product is coated with molten salt to remove molten salt and mineral impurities. The porous carbon crude product is mixed with 5wt% dilute sulfuric acid at a solid-liquid ratio of 1:7 and acid washed at a constant temperature of 80℃ for 3 hours to completely convert the molten salt inside the porous carbon crude product into water-soluble salts. After filtration, the initial solid-liquid separation is completed. The acid-washed solid material is mixed with 4wt% dilute hydrochloric acid and soaked at room temperature for 2 hours to dissolve the potassium aluminum silicate and alumina insoluble mineral impurities remaining in the carbon matrix. After filtration, the secondary solid-liquid separation is completed. The solid material after the removal of molten salt and mineral impurities is rinsed multiple times with deionized water until the pH of the rinsing wastewater is 6.5 and there are no soluble salt residues. After filtration, the solid-liquid separation is completed. Step 8: Place the rinsed carbon material filter cake in a vacuum drying oven and dry at 120℃ for 4 hours to avoid pore collapse caused by high-temperature drying under normal pressure. The moisture content after drying should be ≤1.0%. Then, place the material in a nitrogen atmosphere furnace and passivate at a constant temperature of 760℃ for 40 minutes. Finally, crush, classify, sieve, and demagnetize to obtain the anthracite-based porous carbon negative electrode product. The particle size of the low-ash anthracite-based porous carbon is D10: 4.5μm, D50: 7.8μm, D90: 13.9μm, and D100: 18.8μm. Example 2
[0018] A method for preparing low-ash anthracite-based porous carbon specifically includes the following steps: Step 1: Take high-rank anthracite. The fixed carbon content in the anthracite is 82% by mass, and the ash content is 14.5%. After coarse crushing, put it into a planetary ball mill and crush it to 300 mesh to obtain material 1. Step 2: Add a modifying agent to material 1. The agent is a mixture of citric acid and ammonium fluoride powder. The amount of citric acid added is 1.0 wt% of the coal powder mass, and the amount of ammonium fluoride added is 2.5 wt% of the coal powder mass. Then, use dry mechanical chemical ball milling for 2.5 hours to obtain material 2. Step 3: Mix material 2 with 3wt% dilute sulfuric acid at a solid-liquid ratio of 1:6, stir and soak for 6 hours in a 50℃ water bath to dissolve the calcium, magnesium, and iron inorganic mineral impurities trapped in the anthracite, filter to obtain filter cake, wash the filter cake multiple times with deionized water until the pH of the washing solution is 6.0, dry at 110℃ for 2 hours to obtain pre-deashed clean coal powder, the ash content of the pre-deashed clean coal powder is 1.8%; Step 4: Mix the pre-deashed clean coal powder prepared in Step 3 with the low eutectic composite molten salt in a uniform dry method at a mass ratio of 1:0.8 to obtain a mixed powder. The composite molten salt is a mixture of anhydrous potassium acetate and magnesium nitrate mixed in a mass ratio of 7:3. The eutectic point of the composite molten salt is 215℃. Step 5: Place the mixed powder prepared in Step 4 in a sealed oven with a vacuum degree of -0.08 MPa and keep it at 230℃ for 3 hours. The composite molten salt will completely melt and penetrate into the pores inside the coal powder, forming uniformly distributed nano-salt crystal occupant templates in situ inside the carbon matrix. After natural cooling, crush and granulate the mixture, and screen out granules with a particle size of 10-40 mesh to obtain the molten salt-embedded porous carbon precursor. Step Six: Place the porous carbon precursor prepared in Step Five into a tube furnace, introduce high-purity nitrogen into the tube furnace, and heat it to 550℃ at a heating rate of 4℃ / min. Hold the temperature at this temperature for 90 min to complete the low-temperature carbonization of the anthracite organic matter, precipitate small molecule side chains, initially construct the original pores, and stabilize the internal molten salt grains. Switch the atmosphere in the tube furnace to a weakly oxidizing mixture of nitrogen and 3 vol% dry air, raise the temperature in the tube furnace to 750℃, and hold the temperature at this temperature for 60 min. A small amount of weak oxidation etches the amorphous defect sites of the carbon material, widening the original micropores without causing a large amount of carbon matrix burn-off. Then switch the atmosphere in the tube furnace to a pure carbon dioxide atmosphere, raise the temperature in the tube furnace to 880℃, and hold the temperature at this temperature for 120 min. Carbon dioxide selectively etches the pore edges, precisely amplifies the mesoporous structure, and forms micropore-mesopore composite channels. After activation, allow it to cool naturally to room temperature under a nitrogen protective atmosphere before removing it from the furnace to obtain crude molten salt-coated porous carbon. Step 7: Using a segmented acid washing process, the porous carbon crude product is coated with molten salt to remove molten salt and mineral impurities. The porous carbon crude product is mixed with 5wt% dilute sulfuric acid at a solid-liquid ratio of 1:7 and acid washed at a constant temperature of 80℃ for 3 hours to completely convert the molten salt inside the porous carbon crude product into water-soluble salts. After filtration, the initial solid-liquid separation is completed. The acid-washed solid material is mixed with 4wt% dilute hydrochloric acid and soaked at room temperature for 2 hours to dissolve the residual potassium aluminum silicate and alumina insoluble mineral impurities in the carbon matrix. After filtration, the secondary solid-liquid separation is completed. The solid material after the removal of molten salt and mineral impurities is rinsed multiple times with deionized water until the pH of the rinsing wastewater is 6.8 and there are no soluble salt residues. After filtration, the solid-liquid separation is completed. Step 8: Place the rinsed carbon material filter cake in a vacuum drying oven and dry it at 120℃ for 4 hours to avoid pore collapse caused by high-temperature drying at normal pressure. The moisture content after drying should be ≤1.0%. Then, place the material in a nitrogen atmosphere furnace and passivate it at 760℃ for 90 minutes. Finally, crush, classify, sieve, and demagnetize to obtain the anthracite-based porous carbon negative electrode product. The particle size of the low-ash anthracite-based porous carbon is D10: 4.8μm, D50: 7.1μm, D90: 14.2μm, and D100: 18.9μm. Example 3
[0019] A method for preparing low-ash anthracite-based porous carbon specifically includes the following steps: Step 1: Take high-rank anthracite. The fixed carbon content in the anthracite is 90% by mass and the ash content is 7.5%. After coarse crushing, put it into a planetary ball mill and crush it to 400 mesh to obtain material 1. Step 2: Add a modifying agent to material 1. The agent is a mixture of citric acid and ammonium fluoride powder. The amount of citric acid added is 1.0 wt% of the coal powder mass, and the amount of ammonium fluoride added is 2.5 wt% of the coal powder mass. Then, use dry mechanical chemical ball milling for 4 hours to obtain material 2. Step 3: Mix material 2 with 5wt% dilute sulfuric acid at a solid-liquid ratio of 1:6, stir and soak in a 60℃ water bath for 4 hours to dissolve the calcium, magnesium, and iron inorganic mineral impurities trapped in the anthracite, filter to obtain filter cake, wash the filter cake multiple times with deionized water until the pH of the washing solution is 7.0, dry at 110℃ for 10 hours to obtain pre-deashed clean coal powder, the ash content of the pre-deashed clean coal powder is 0.8%; Step 4: Mix the pre-deashed clean coal powder prepared in Step 3 with the low eutectic composite molten salt at a mass ratio of 1:1.2 using a uniform dry method to obtain a mixed powder. The composite molten salt is a mixture of anhydrous potassium acetate and magnesium nitrate mixed at a mass ratio of 7:3. The eutectic point of the composite molten salt is 215℃. Step 5: Place the mixed powder prepared in Step 4 in a sealed oven with a vacuum degree of -0.08 MPa and keep it at 250℃ for 3 hours. The composite molten salt will completely melt and penetrate into the pores inside the coal powder, forming uniformly distributed nano-salt crystal occupant templates in situ inside the carbon matrix. After natural cooling, crush and granulate the material, and screen out granules with a particle size of 10-40 mesh to obtain the molten salt-embedded porous carbon precursor. Step Six: Place the porous carbon precursor prepared in Step Five into a rotary kiln, introduce high-purity nitrogen into the kiln, and heat it to 550℃ at a heating rate of 4℃ / min. Hold the temperature at this temperature for 90 min to complete the low-temperature carbonization of the anthracite organic matter, precipitate small molecule side chains, initially construct the original pores, and stabilize the internal molten salt grains. Switch the atmosphere in the rotary kiln to a weakly oxidizing mixture of nitrogen and 5 vol% dry air, raise the temperature in the rotary kiln to 750℃, and hold the temperature at this temperature for 60 min. A small amount of weak oxidation etches the amorphous defect sites of the carbon material, widening the original micropores without causing a large amount of carbon matrix burn-off. Then switch the atmosphere in the rotary kiln to a pure carbon dioxide atmosphere, raise the temperature in the rotary kiln to 880℃, and hold the temperature at this temperature for 180 min. Carbon dioxide selectively etches the pore edges, precisely amplifies the mesoporous structure, and forms micropore-mesopore composite channels. After activation, allow it to cool naturally to room temperature under a nitrogen protective atmosphere before removing it from the kiln to obtain the crude porous carbon coated with molten salt. Step 7: Using a segmented acid washing process, the porous carbon crude product is coated with molten salt to remove molten salt and mineral impurities. The porous carbon crude product is mixed with 5wt% dilute sulfuric acid at a solid-liquid ratio of 1:7 and acid washed at a constant temperature of 80℃ for 3 hours to completely convert the molten salt inside the porous carbon crude product into water-soluble salts. After filtration, the initial solid-liquid separation is completed. The acid-washed solid material is mixed with 4wt% dilute hydrochloric acid and soaked at room temperature for 2 hours to dissolve the potassium aluminum silicate and alumina insoluble mineral impurities remaining in the carbon matrix. After filtration, the secondary solid-liquid separation is completed. The solid material after the removal of molten salt and mineral impurities is rinsed multiple times with deionized water until the pH of the rinsing wastewater is 7.2 and there are no soluble salt residues. After filtration, the solid-liquid separation is completed. Step 8: Place the rinsed carbon material filter cake in a vacuum drying oven and vacuum dry at 120℃ for 4 hours to avoid pore collapse caused by high-temperature drying at normal pressure. The moisture content after drying should be ≤1.0%. Then, place the material in a nitrogen atmosphere furnace and passivate at a constant temperature of 760℃ for 60 minutes. Finally, crush, classify, sieve, and demagnetize to obtain the anthracite-based porous carbon anode product. The particle size of the low-ash anthracite-based porous carbon is D10: 4.5μm, D50: 7.9μm, D90: 14.1μm, and D100: 18.6μm.
[0020] Comparative Example 1: Traditional KOH High-Temperature Alkali Activation Process Anthracite from Example 1 was crushed and screened, then mixed with KOH at a mass ratio of 1:4 using a dry method. The mixture was activated at a constant temperature of 780℃ for 150 minutes under a nitrogen atmosphere. After being removed from the furnace, it was washed with hydrochloric acid, washed with water, and dried.
[0021] Comparative Example 2: Single CO2 physical activation process Anthracite from Example 1, with an ash content of 1.2%, was pre-carbonized and then activated at a constant temperature of 900°C for 7 hours in a pure CO2 atmosphere, followed by conventional acid washing to remove impurities and drying.
[0022] Anthracite-based porous carbon anode products prepared in Examples 1-3 and Comparative Examples 1-2 were tested under the same conditions using a high-performance specific surface area and micropore analyzer to measure BET, pore volume, average pore size, and microporosity. At the same time, the ash content of the anthracite porous carbon was tested using a muffle furnace, and the yield of porous carbon was calculated. The results are listed in Table 1.
[0023] Table 1 Performance parameters of anthracite-based porous carbon anode products
[0024] Based on the experimental data in Table 1, it can be seen that the porous carbon prepared in Examples 1-3 all had lower ash content than Comparative Examples 1 and 2, and the porous carbon yield was also significantly higher than that of Comparative Examples 1 and 2. Their specific surface area and pore volume were comparable to Comparative Example 1, indicating similar adsorption capacities. In terms of pore size distribution, Examples 1 and 2 showed a higher proportion of ultramicropores below 0.7 nm, which is beneficial for improving adsorption capacity. Example 3, by adjusting process parameters, achieved a reasonable distribution of pore structures within different pore size ranges. The appropriate increase in the proportion of mesopores further facilitated rapid ion transport and improved adaptability to anode application scenarios.
[0025] Comparative Example 1, using a traditional KOH activation process, achieved a high specific surface area, but the carbon matrix suffered severe ablation during activation, resulting in a yield of less than 23%, high production costs, and a higher ash content in the finished product compared to the method described in this invention. Comparative Example 2, employing only CO2 physical activation, yielded porous carbon with significantly lower specific surface area and total pore volume, a lower proportion of micropores, and insufficient pore structure development. It also had a lower yield and higher ash content, making its overall performance far inferior to the product of the embodiments of this invention. This demonstrates that the low eutectic salt occupancy combined with stepwise etching activation process employed in this invention can achieve high yield and low ash content while obtaining anthracite-based porous carbon with well-developed pore structure and reasonable pore size distribution.
[0026] Comparing the data from each embodiment, Example 3, which uses anthracite with a higher primary carbon content as raw material, produced the porous carbon with the lowest ash content and a relatively high yield, demonstrating the most outstanding overall performance among the three embodiments.
[0027] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Any other modifications or equivalent substitutions made by those skilled in the art to the technical solutions of the present invention, as long as they do not depart from the spirit and scope of the technical solutions of the present invention, should be covered within the scope of the claims of the present invention.
Claims
1. A method for preparing low-ash anthracite-based porous carbon, characterized in that, Specifically, the following steps are included: Step 1: Take high-rank anthracite, coarsely crush it, and then put it into a planetary ball mill to grind it to 300-400 mesh to obtain material 1; Step 2: Add the modifying agent to material 1, and then use dry mechanical chemical ball milling for 2-4 hours to obtain material 2; Step 3: Mix and soak material 2 with acid solution to dissolve the calcium, magnesium and iron inorganic mineral impurities trapped in the anthracite coal, filter to obtain filter cake, wash the filter cake with deionized water until neutral and then dry to obtain pre-ashed clean coal powder. Step 4: Mix the pre-deashed clean coal powder prepared in Step 3 with the eutectic composite molten salt at a mass ratio of 1:0.8-1.2 using a uniform dry method to obtain the mixed powder. Step 5: Place the mixed powder prepared in Step 4 in a sealed oven and keep it at a constant temperature of 230-250℃ for 3-8 hours. The composite molten salt will completely melt and penetrate into the pores inside the coal powder, forming a uniformly distributed nano-salt crystal occupant template in situ inside the carbon matrix. After natural cooling, crush and granulate the mixture, and screen out granules with a particle size of 10-40 mesh to obtain the molten salt-embedded porous carbon precursor. Step Six: Place the porous carbon precursor prepared in Step Five into a rotary kiln or tubular furnace, and activate and carbonize it using a three-stage gradient heating and segmented atmosphere switching process at a heating rate of 4℃ / min. The temperature curve is as follows: The first stage, the inert pre-carbonization stage: high-purity nitrogen gas is introduced into the rotary kiln or tubular furnace, the temperature is raised to 550℃, and the temperature is kept constant for 60-90 minutes to complete the low-temperature carbonization of the anthracite organic matter, precipitate small molecule side chains, initially construct the original pores, and stabilize the internal molten salt grains. The second stage, the weak oxidation repair stage: the atmosphere in the rotary kiln or tubular furnace is switched to a weak oxidation mixture of nitrogen + (3~5) vol% dry air, and the temperature in the rotary kiln or tubular furnace is raised from 550℃ to 750℃ and kept at a constant temperature for 60~90min. The third stage, CO2 fine pore expansion stage: The atmosphere in the rotary kiln or tubular furnace is switched to pure carbon dioxide atmosphere, the temperature in the rotary kiln or tubular furnace is raised from 750℃ to 880℃, and the temperature is kept constant for 120 to 180 minutes. Carbon dioxide selectively etches the edge of the pores, precisely expands the mesoporous structure, and forms micropore-mesopore composite pores. After activation, the furnace is naturally cooled to room temperature under a nitrogen protective atmosphere to obtain molten salt coated porous carbon crude product. Step 7: Pickling the porous carbon crude product coated with molten salt removes molten salt and mineral impurities. The solid material after removing molten salt and mineral impurities is rinsed multiple times with deionized water until the pH of the rinsing wastewater is 6.5-7.2 and there are no soluble salt residues. Filter and separate the solid and liquid. Step 8: Place the rinsed carbon material filter cake in a vacuum drying oven and dry it at 120℃ for 2-10 hours. Then, place the material in a nitrogen atmosphere furnace and passivate it at 760℃ for 40-90 minutes. Finally, crush, classify, sieve, and demagnetize to obtain the anthracite-based porous carbon anode product.
2. The method for preparing low-ash anthracite-based porous carbon according to claim 1, characterized in that, In step one, the fixed carbon content in anthracite is 82%–90% by mass, and the ash content in anthracite is 7%–15% by mass.
3. The method for preparing low-ash anthracite-based porous carbon according to claim 1, characterized in that, In step two, the additive is a mixture of citric acid and ammonium fluoride powder. The amount of citric acid added is 1.0 wt% of the coal powder mass, and the amount of ammonium fluoride added is 2.5 wt% of the coal powder mass.
4. The method for preparing low-ash anthracite-based porous carbon according to claim 1, characterized in that, In step three, the ash content of the pre-deashed clean coal powder is 0.8% to 1.8%.
5. The method for preparing low-ash anthracite-based porous carbon according to claim 1, characterized in that, In step three, material two is mixed with 3-5 wt% dilute sulfuric acid at a solid-liquid ratio of 1:6, stirred and soaked in a water bath at 50℃-80℃ for 4-6 hours, filtered to obtain a filter cake, and washed with deionized water multiple times until the pH of the washing solution is 6.0-7.
0. The washed filter cake is then dried at 110℃ for 2-10 hours.
6. The method for preparing low-ash anthracite-based porous carbon according to claim 1, characterized in that, In step four, the composite molten salt is a mixture of anhydrous potassium acetate and magnesium nitrate mixed in a 7:3 mass ratio, and the eutectic point of the composite molten salt is 215℃.
7. The method for preparing low-ash anthracite-based porous carbon according to claim 1, characterized in that, In step five, the vacuum degree of the sealed oven is -0.08MPa.
8. The method for preparing low-ash anthracite-based porous carbon according to claim 1, characterized in that, The specific pickling steps in step seven are as follows: First-stage sulfuric acid removal of molten salt: Mix the porous carbon crude product with 5wt% dilute sulfuric acid at a solid-liquid ratio of 1:7, stir and acid wash at 80℃ for 2-5 hours to completely convert the molten salt inside the porous carbon crude product into water-soluble salts and dissolve them. Filter to complete the preliminary solid-liquid separation. Secondary hydrochloric acid demineralization: The acid-washed solid material is mixed with 4wt% dilute hydrochloric acid and soaked at room temperature for 2-5 hours to dissolve the potassium aluminum silicate and alumina insoluble mineral impurities remaining in the carbon matrix. After filtration, the secondary solid-liquid separation is completed.
9. A low-ash anthracite-based porous carbon, characterized in that, The low-ash anthracite-based porous carbon is prepared by the method for preparing low-ash anthracite-based porous carbon according to any one of claims 1-8.
10. The low-ash anthracite-based porous carbon according to claim 9, characterized in that, The particle size of the low-ash anthracite-based porous carbon is D10: ≥4.5μm, D50: 7.0-8.0μm, D90≤15μm, and D100≤20μm.